Case report: Eosinophilic pneumonia associated with vedolizumab therapy in a patient with ulcerative colitis - Zhu, Wanwan; Zhao, Tianhao; Wei, Jun; Chai, Damin; Zhao, Cancan; Zhu, Yu; Deng, Min (Frontiers in Medicine, 2022)
Extraintestinal manifestations are common in patients with inflammatory bowel disease, while respiratory involvement is less common. Vedolizumab is a newer class of anti-integrin biological agents approved to treat inflammatory bowel disease. In this report, we present the case of a 38-year-old patient with ulcerative colitis for 7 years, who developed cough, fever, and pulmonary infiltrates after taking vedolizumab. There was a spontaneous improvement in clinical symptoms and radiological abnormalities after discontinuing vedolizumab and introducing steroids. Despite the rarity of vedolizumab-induced eosinophilic pneumonia, the case reports indicate that patients with unexplained respiratory symptoms that are taking vedolizumab should be fully contemplated.